Learning from the Joneses: The professional learning effect of regional councils of government on municipal fiscal slack in suburban Chicago. (30th October 2020) - Mitchell, David; Davis, Whitney; Hendrick, Rebecca
Abstract: Fiscal slack scholars have sought to identify the primary generators of unreserved fund balance (UFB) within local governments, including economic, organizational, demographic, institutional, and political factors. Guo and Wang extend this endeavor spatially; however, geography may mask the professional learning impact of subregional councils of governments (COGs). This study examines 265 Chicago suburban municipalities to reveal through a pairing approach that municipalities who belong to the same subregional COG generally have more similar UFB levels, independent of geographical proximity. Policymakers can therefore utilize COGs when making decisions regarding a municipality's most vital resource for strategic investments and fiscal stress. Applications for Practice: Municipal officials should not only look to adjacent communities to benchmark tax and fiscal policy instruments such as fund balance reserves but also peer members within councils of government. Fiscal policy is not driven solely by competitive motivations; professional norms also have a significant impact on the fiscal preferences of municipal officials. The import of best practices via councils of government may promote a more informed and transparent fiscal deliberation that includes and welcomes not only political but also professional viewpoints.